Pyloric Obstruction Caused by an Inflammatory Fibroid Polyp. (6th May 2019) - Mantas, Dimitrios; Garmpis, Nikolaos; Polychroni, Damaskini; Garmpi, Anna; Damaskos, Christos; Kouskos, Efstratios
Abstract : This is a case report of a 57-year-old woman who presented with abdominal pain and vomiting over a period of two months. Upper gastrointestinal endoscopies and biopsies were inconclusive, while abdomen computed tomography (CT) scan revealed a large mass arising from the pyloric antrum measuring about6 × 4.8 cm imitating gastrointestinal stromal tumor (GIST). The patient underwent a laparotomy, and the tumor was totally resected with well-defined borders. The histopathological analysis revealed the mass to be an inflammatory fibroid polyp (IFP).